2016
DOI: 10.1002/jrs.4885
|View full text |Cite
|
Sign up to set email alerts
|

Probing conformational propensities of histidine in different protonation states of the unblocked glycyl‐histidyl‐glycine peptide by vibrational and NMR spectroscopy

Abstract: Histidine has been shown to play a major role in a number of biological systems. Being able to understand unconstrained conformational distributions of histidine and their dependence on the environment can shed light on the structure–function relation with regard to its multiple roles in biochemical processes such as proton transfer, ligand binding, protein folding and maintaining protein intrinsic disorder. We utilized polarized Raman, FTIR, vibrational circular dichroism and 1H NMR spectroscopy to probe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 92 publications
0
23
0
Order By: Relevance
“…3b). Interestingly, a recent study of single and double protonated histidine residue in GHG in water revealed an equidistribution in the pPII and b-strand regions similar to the ones for F and Y [60]. The Gaussian distributions of F and Y also feature minor basins of conformations on the right side of the Ramachandran plot (f 4 0).…”
Section: Ramachandran Distributions and Mesostate Populationsmentioning
confidence: 77%
“…3b). Interestingly, a recent study of single and double protonated histidine residue in GHG in water revealed an equidistribution in the pPII and b-strand regions similar to the ones for F and Y [60]. The Gaussian distributions of F and Y also feature minor basins of conformations on the right side of the Ramachandran plot (f 4 0).…”
Section: Ramachandran Distributions and Mesostate Populationsmentioning
confidence: 77%
“…However, several peptides without aromaticity have been shown to readily self‐assemble into fibril networks. For example, glycine‐alanine‐glycine (GAG) and glycine‐histidine‐glycine (GHG) self‐assemble into very long microfibrils under the right conditions 19–26 . More specifically, GAG forms fibrils in the presence of a critical fraction of ethanol that depends on peptide concentration 26 .…”
Section: Introductionmentioning
confidence: 99%
“…H-bonding has recently been shown to play a critical role in the gelation of a small peptide hydrogelator, GHG. 31 Involvement of the Tyr side chain hydroxyl group in H-bonding is often characterized using Raman spectroscopy. Tyrosine generates a pair of fairly intense Raman bands at ∼850 and 830 cm −1 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%